Silent nights are murder - Klein, Libby (Mystery author) (Klein, Libby (Mystery author). Poppy McAllister mystery., 2024)
"Ever since Thanksgiving, when an engagement ring in a velvet box--and no gift tag--was left behind, Poppy and her pals have been left with an unsolved mystery. But at least this mystery isn't the kind that involves murder. That all changes when the body of a fish supplier is discovered in the kitchen of her ex's restaurant--and he's frozen, not fresh. For once, it's not Poppy who tripped over the corpse, yet she can't escape being drawn in since the victim has a note taped to him reading Get Poppy. Figures--an engagement ring isn't labeled, but the dead guy is addressed to her. Now, while Aunt Ginny plans a tree-trimming party and pressures Poppy to decode a mysterious old diary, the amateur sleuth is asked to "unofficially" go undercover at the restaurant to help the police. Until then, the only crime Poppy had been dealing with was the cat Figaro's repeated thefts of bird ornaments from the tree; now it looks like it's going to be a murder-y Christmas after all..."--